Autoria na pregação religiosa neopentecostal - Silva, Elias Coelho da (2016)
Language is a dialogical activity in its constitution, and this is the most important Bakhtin’s concept. When using the language, one dives into a universal symposium where his or her voice always meet the voice of the other, and together, they create the speech. For this reason, in the discursive role, we never find a single voice, but a diversity of people's voices. We need to interact with all these voices and we creat our own among these voices. However, according to Bakhtin, in some areas of human activity the dialogue with the other’s word is restricted, and this is the case of religious speech, where the word has a special weight and does not allow it to be used in vain, it is compact and inert, and one should accept it or reject it. So, how can we authoring our voice in the middle of words that require passivity and obedience? Based on Bakhtin's conception, we tried to investigate the speech’s authorship in religious preaching. Our aim in this research is to understand how the process of speech’s authorship is constituted in neo-Pentecostal preaching. For this reason, we also aim to identify, describe and explain how function the different voices inside the speech of the author-preacher. It develops, depending on the object of study, a qualitative research responsive character, through a documentary research. Our research corpus consists of five speeches of preaching, and one of these sample is analyzed. To perform the analysis, transcripts were made from what was said in the worship speeches, than after , different voices found in it were selected. We are based on theoretical and methodological Bakhtin studies of language, from where we take the analytical categories that constitute what we call ‘authorship’s architeture’ and we are also based on the ways of transmission of another's speech. The results show us that authoring into this specific genre of speech means to accept an axiological position that reflects and refracts values through a complex process of selection, organization and distribution of other's voices. This process is marked more for the appropriation and simulation of other’s voice than through the passive obedience to religious authoritarian word.